2021
DOI: 10.1177/0022034521995798
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure Disrupts Enamel Formation via EZH2-Mediated H3K27me3

Abstract: Enamel formation is a serial and complex biological process, during which related genes are expressed progressively in a spatiotemporal manner. This process is vulnerable to environmental cues, resulting in developmental defects of enamel (DDE). However, how environmental factors are biologically integrated during enamel formation is still poorly understood. Here, we investigated the mechanism of DDE elicited by a model endocrine-disrupting chemical, bisphenol A (BPA), in mouse incisors. We show that BPA expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…The first studies were published in 2010 24,25 and the most recent studies were published in 2021. 26 The studies have different aims and designs. The dental enamel formation occurs within a series of precisely regulated and timed molecular, biochemical and cellular events.…”
Section: Data Items and Syntheses Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first studies were published in 2010 24,25 and the most recent studies were published in 2021. 26 The studies have different aims and designs. The dental enamel formation occurs within a series of precisely regulated and timed molecular, biochemical and cellular events.…”
Section: Data Items and Syntheses Of The Resultsmentioning
confidence: 99%
“…The elicitation of enamel defects by environmental factors has been the focus of research and debate. 5 The included study from Li et al ( 2021) 26 the authors explored the impact of a common environmental factor in the enamel formation using an in vivo and in vitro design. They explored the connection between Bisphenol A (BPA), which is a well-known endocrine-disrupting chemical, with enamel defect.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Estrogen, which acts through its alpha (ESR1) and beta (ESR2) receptors, promotes the deposition of calcium and phosphorus in bones and plays an important role in the stimulation of osteoblast activity [ 40 , 41 ]. The localization and a pattern of distribution of ER1 immunoreactions in rat ameloblasts throughout the stages of amelogenesis and the involvement of ER1 in epigenetic regulations in pre-ameloblast of the cervical loop of mouse incisors have been demonstrated [ 42 , 43 , 44 ]. ESR1 rs2234693 was analyzed by four groups with different results.…”
Section: Discussionmentioning
confidence: 99%
“…This work demonstrated that H3K27me3 highly occupies within the transcript start region of Shh, thus repressing its transcription ( 15 ). Besides, our previous study also showed that Shh-resident regions were weakly modified by H3K27me3, suggesting that H3K27me3 may also play an upstream restraining role for Shh expression in incisor epithelium ( 16 ). As a repressive histone modification, H3K27me3 has been proposed to regulate self-renewal, lineage specification, and survival of diverse kinds of stem cells, indicating its indispensable functions on stem cell fate determination ( 17 20 ).…”
Section: Introductionmentioning
confidence: 90%